2015
DOI: 10.4238/2015.february.20.2
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Characterization of chloroplast region rrn16-rrn23S from the tropical timber tree Cedrela odorata L. and de novo construction of a transplastomic expression vector suitable for Meliaceae trees and other economically important crops

Abstract: ABSTRACT. The forest tree Spanish cedar (Cedrela odorata L.) is well-known for its high-value timber; however, this species is attacked by the shoot borer (Hypsipyla grandella) during its early years of development, resulting in branched stems and making the plants useless for high-quality wood production. The generation of resistant varieties expressing entomotoxic proteins may be an alternative to pesticide treatments. The use of plastid transformation rather than nuclear transformation should be used becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Conversely, as a consequence of gene transfer events, the original functional gene sequence of ndhF was relocated to the exon region of nad5 . The rrn16 - rrn23 regions were used to construct transformation vectors, indicating that the rrn16 - rrn23 chloroplast region might affect transformation efficiency ( Lopez-Ochoa et al., 2015 ). The lost tRNAs in mitogenomes can be replaced by tRNAs inserted into other organelles ( Sloan et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, as a consequence of gene transfer events, the original functional gene sequence of ndhF was relocated to the exon region of nad5 . The rrn16 - rrn23 regions were used to construct transformation vectors, indicating that the rrn16 - rrn23 chloroplast region might affect transformation efficiency ( Lopez-Ochoa et al., 2015 ). The lost tRNAs in mitogenomes can be replaced by tRNAs inserted into other organelles ( Sloan et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current experiment, we successfully screened the transplastomic lines of S. dulcis using an efficient selection process on spectinomycin antibiotic. Stable integration of chloroplast transformation was achieved in tobacco, lettuce, Cedrelaodorata, Capsicum and Marchantia polymorpha L. using the insertion sites of trnA and trnI fragments from IR region (Bock and Maliga 1995;Chiyoda et al 2007;K Mühlbauer et al 2002;Lelivelt et al 2005;López-Ochoa et al 2015;Staub and Maliga 1992). In our lab, the same trnA/trnI of IR region was targeted to recover transplastomic lines of Momordica charantia by a Cucumis sativus based heterologous vector (CuIA) (Narra et al 2018b) and obtained 2 transplastomic lines from 15 bombarded plates using petiole explants.…”
Section: Discussionmentioning
confidence: 99%
“…The first ever high-frequency plastid transformation was successfully established in Nicotiana tabacum (Svab et al 1990) and many other reports revealed its suitability as model experimental plant system for chloroplast transformation (Gottschamel et al 2013). Apart from tobacco, chloroplast transformation was also reported in other plants such as potato (Sidorov et al 1999), rapeseed (Cheng et al 2010), tomato (Ruf et al 2001), cabbage (Liu et al 2007), lettuce (Lelivelt et al 2005), rice (Lee et al 2006), Cedrela odorata (López-Ochoa et al 2015), scoparia (Muralikrishna et al 2016), and bitter melon (Narra et al 2018). However, the development of chloroplast transformation has been extended to many other plant systems, until today, this technology remains challenging and limited to achieve due to Srinivas Kota and Raghuvardhan Lakkam contributed equally.…”
Section: Introductionmentioning
confidence: 99%
“…The trnfM and trnG sites of LSC region were used to design the chloroplast transformation vector in tobacco (Bock and Maliga 1995;Madanala et al 2012) and tomato (Ruf et al 2001). In addition, trnA and trnI fragments from IR region were used to develop new chloroplast transformation vector in tobacco (Bock andMaliga 1995, K Mühlbauer et al 2002;Staub and Maliga 1992), and other species such as lettuce (Lelivelt et al 2005), Marchantia polymorpha L. (Chiyoda et al 2007), and Cedrela odorata (López-Ochoa et al 2015). Construction of speciesspecific plastid vectors is not always necessary, as the plastid genome is very conserved among different plant species, but they will significantly increase transformation efficiency (Maliga 2004;Svab et al 1990).…”
Section: Introductionmentioning
confidence: 99%